2017
DOI: 10.1039/c7ra03323k
|View full text |Cite
|
Sign up to set email alerts
|

Coalescence of droplets on micro-structure patterned hydrophobic planar solid surfaces

Abstract: The motion and coalescence of sessile liquid droplets on patterned solid surfaces are investigated systematically in terms of the liquid and substrate surface properties. A patterned silicon surface is decorated with circular pillars. The fabrication of the substrate is carried out by following standard photolithography. A thin photoresist layer of AZ-9260 on the pillars makes the surface exhibit superhydrophobic properties. The pillars are obtained using a deep reactive-ion etching process. Due to the deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…There are so many studies that have focused on the effect of surface structures. Zhu et al 23 investigated the coalescence dynamics of droplets on microtextured surfaces decorated with circular pillared structures that have different sizes (i.e., different intervals and diameters). It was found that the substrates would exhibit stronger hydrophobicity when the interval of pillars is large, and thus accelerate the coalescing process.…”
Section: ■ Introductionmentioning
confidence: 99%
“…There are so many studies that have focused on the effect of surface structures. Zhu et al 23 investigated the coalescence dynamics of droplets on microtextured surfaces decorated with circular pillared structures that have different sizes (i.e., different intervals and diameters). It was found that the substrates would exhibit stronger hydrophobicity when the interval of pillars is large, and thus accelerate the coalescing process.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Since then, numerous papers on sessile drop coalescence have appeared. Topics of investigation have included power law growth of the liquid bridge after coalescence initiation [17,18,19,20,21,22,23], overall shape evolution [7,24,25,26,27,28,29,30], and long-time contact line relaxation dynamics [31,32,33,34,35]. Following the 2009 discovery of self-propelled dropwise condensate removal on superhydrophobic surfaces [36,37], a majority of these studies have explored coalescence-induced out-of-plane drop jumping [38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60 For their utility in interpreting experimental observations, computational fluid dynamics simulations of sessile drop coalescence have also become popular over the last decade…”
Section: Introductionmentioning
confidence: 99%
“…Microsized droplet manipulations such as droplet storage, transfer, and mixing have attracted considerable attention due to their great potential applications in high throughput cell screening, biochemical synthesis, molecular sensing, , and other lab-on-a-chip devices. , For instance, spherical droplet arrays pinned on a solid surface can serve as miniature vessels to culture cells for high throughput cell transfection and drug screening. In comparison with microplate technology, the above methods can reduce reagents and cell consumption by 15000 times . Seeding molecules for detection into the droplet and enriching the droplet by controlled volatilization can greatly increase the molecular target concentration in the droplet, increase the reaction probability of the probe and target, and thus improve the detection accuracy of the molecular target.…”
Section: Introductionmentioning
confidence: 99%